2012
DOI: 10.4315/0362-028x.jfp-11-458
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Antimicrobial Resistance Profiles of Salmonella from Commercial Broiler Farms in Two Important Poultry-Producing Regions of Colombia

Abstract: Salmonella is one of the most common foodborne pathogens associated with diarrheal disease in humans. Food animals, especially poultry, are important direct and indirect sources of human salmonellosis, and antimicrobial resistance is an emerging problem of public health concern. The use of antimicrobials benefits producers but contributes to the emergence of antimicrobial resistant bacteria. As a step toward implementing the Colombian Integrated Program for Antimicrobial Resistance Surveillance, this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 28 publications
10
37
0
2
Order By: Relevance
“…A variety of Salmonella serovars resistant to multiple antibiotic classes were present in chicken meat samples and a high percentage (42.35%) of Salmonella showed multi-drug resistance (MDR) by the phenotypic method, among them, all S. Paratyphi B isolates and S. Heildelberg were resistant to 7 different classes of antibiotics, whereas S. Muenster and S. Typhimurium were resistant to 4 different classes of antibiotics. These results are similar to those reported in Salmonella Paratyphi B isolated from broiler farms in Cundinamarca and Santander, where this serovar was found to be resistant to up to 15 antimicrobials (range 9-15) (Donado-Godoy et al, 2012), of which resistance to NIT, SXT, TET, CIP and ENR can be identified as a common resistance pattern that is consistent at least in part with the usage of tetracycline, trimethoprim and quinolones in the regional poultry industry (based on author´s survey). Thus, the choice of fluoroquinolones in treatment of severe infections by Salmonella could be seriously impeded, as it has been noted by others (Ricke & Calo, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A variety of Salmonella serovars resistant to multiple antibiotic classes were present in chicken meat samples and a high percentage (42.35%) of Salmonella showed multi-drug resistance (MDR) by the phenotypic method, among them, all S. Paratyphi B isolates and S. Heildelberg were resistant to 7 different classes of antibiotics, whereas S. Muenster and S. Typhimurium were resistant to 4 different classes of antibiotics. These results are similar to those reported in Salmonella Paratyphi B isolated from broiler farms in Cundinamarca and Santander, where this serovar was found to be resistant to up to 15 antimicrobials (range 9-15) (Donado-Godoy et al, 2012), of which resistance to NIT, SXT, TET, CIP and ENR can be identified as a common resistance pattern that is consistent at least in part with the usage of tetracycline, trimethoprim and quinolones in the regional poultry industry (based on author´s survey). Thus, the choice of fluoroquinolones in treatment of severe infections by Salmonella could be seriously impeded, as it has been noted by others (Ricke & Calo, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Salmonella Enteritidis and S. Typhimurium are the most widespread serovars and can be isolated from surface water, meat and poultry (Jokinen et al, 2015;Yang et al, 2010), and constitute the principal serovars responsible for human and animal disease (MPS, 2011;Stevens et al, 2009), however, our previous study reported that Salmonella Enteritidis was not isolated from chicken meat sold at stores and supermarkets of Ibague, and instead Salmonella Paratyphi B var Java was the most prevalent serovar (36.17%) followed by Hvittingfoss (19.15%), and Muenster (10.64%) (Rodriguez et al, 2015b). S. Paratyphi B variant Java (76.4%) and S. Heildelberg (22.7%) were the most prevalent serovars isolated from broiler farms in two distinct regions (Cundinamarca and Santander) of Colombia (Donado-Godoy et al, 2012), thus, this serovar might be distributed in broiler farms across the country and its potential association with natural outbreaks of paratyphoid disease reported by the National Institute of Health (INS, 2015), is worthy of investigation. S. Paratyphi B var Java has been isolated from poultry from Netherlands (Van Pelt et al, 2003) and Germany (Dorn et al, 2001), from chicken viscera at two slaughter plants in the state of Zulia, Venezuela (Boscan et al, 2005), from chicken in Belgium (De Jong et al, 2014), and from breeders and broiler farms in Bangladesh (Barua et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Controlling Salmonella in poultry is problematic, and it has relied historically on a combination of farm biosecurity and the use of antibiotics [10]. The indiscriminate and injudicious use of antibiotics is an important factor in the emergence of antibiotic-resistant bacteria that subsequently can be transferred to humans through the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…1) reflects the magnitude of the health risk (6,29). Although some classes of drugs have been banned from use in animal feed in Brazil, such as tetracyclines (18) and phenicols (19), during the study period, strains resistant to these drugs were still detected at prevalences of 17.5 and -4%, respectively.…”
Section: Discussionmentioning
confidence: 99%